MECHANICAL APPROACH AS ERROR PROOFING TO PREVENT WRONG ORIENTATION OF PRODUCT - Arif Rahman Hakim (JURNAL DIMENSI, 2016)
Error or mistake is occurred in such away that causing product malfunction, machine not working, process produce defective. All of these affect the quality and productivity, further more will increase cost of production.Many aspects can create error, such as human, design, process, raw material, method and environment. A lot of effort put in place to prevent or eliminate error. Detection by inspection is old method applied in industry. Detection can be applied pre production or post production. Both of method has their own advantages. Inspection prior production will ensure the input are free from defect, while inspection post production is to prevent defect escape to customer.In many industries nowdays, inspection still being carried out by human. This type of inspection has been affected by human capability which is very hard to be consistent at all time. In Integrated Circuit Assembly manufacturing, some problem may happen due to wrong orientation and or misalignment of production part. This research is carried out in one of IC assembly manufacture in Batam.